Penerapan Standar Nasional Indonesia (SNI) dalam Tata Kelola Arsip di Perguruan Tinggi - Sri Junandi; Dwiyantoro Dwiyantoro; Bayu Setiawan (Direktorat Perpustakaan Universitas Islam Indonesia, 2022)
Currently in Indonesia, most agencies/institutions have not carried out the archive management process using SNI/ISO standards. It is time for effective and efficient archive management to be implemented. This study aims to describe archive management by applying SNI/ISO 30301, 23081, and 15489 standards at the University of Indonesia Archives Office, the benefits obtained, the obstacles faced and the supporting factors in the implementation process. The research method used is descriptive, namely describing the process of applying SNI/ISO standards 30301, 23081, and 15489 at the University of Indonesia Archives Office which includes policies, responsibilities, monitoring and evaluation, risk assessment/management, training and competence, recording control, making processes , capture and manage records. In addition, the study also describes the benefits obtained and the obstacles faced as well as the supporting factors. The application of SNI/ISO 30301, 23081, and 15489 in managing archives is an indicator/requirement as a benchmark in managing archives effectively and efficiently.